Relationship between the Production Traits and three Candidate Genes in the Prolactin’s In/Del×In/Del Population of Silkie Fowl - MD. Mijanur Rahman; Riho Matsuda; Tomoe Matsuda; Yuki Nishiyama; Kosuke Jozaki; Kajio Anann; Yasuhiko Wada (The Journal of Poultry Science, 2014)
Silkie fowl are very famous in China and Japan, however the egg production rate of the Silkie fowl is very low because of broodiness. Authors have examined the polymorphisms of the 5′-flanking region of the prolactin gene in Taihe Silkie fowl and identified a 24-bp In/Del locus, but no In/In Silkie individuals have been found. In this study, In/In individuals were constructed from an In/Del×In/Del population in order to examine the unique characteristics of Silkies. The relationships between production traits and DNA markers of the three candidate genes were studied. To produce In/In Silkie individuals, male and female individuals with the In/Del locus in the fourth generation of the Silkie fowl selection population were crossed. Genotyping was performed for the prolactin In/Del locus, the DNA marker of neuropeptide Y, and the dopamine D2 receptor. In this study, 27 Del/Del, 39 In/Del, and 21 In/In female individuals and 13 Del/Del, 26 In/Del, and 17 In/In male individuals were found. All In/In individuals had the Silkie fowl characteristics. A significant effect of neuropeptide Y was found on eggshell strength (p<0.05) in female birds, and a significant effect of prolactin and dopamine D2 receptor gene was found on the body weight at 50 day in male birds (p<0.05).